Gel polymer electrolyte matrix material, electrolyte and battery

Through organic sulfonate polyethylene polyvinyl alcohol and n, N-di ethylene cyanocyline free radical polymerization, prepare a gel polymer electrolytic substrate material, which solves the contradiction between the conductivity and mechanical performance in the existing technology The problem realizes the consideration of high -tech guidance and good mechanical properties.

CN114709476BActive Publication Date: 2025-01-28CHENGDU YIANG TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210317418.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-29
Publication Date
2025-01-28
Estimated Expiration
2042-03-29

AI Technical Summary

Technical Problem

While the existing gel polymer electrolytes improve ionic conductivity, their mechanical strength becomes worse, making it difficult to meet the needs of high conductivity and good mechanical properties at the same time.

Method used

Adopt organic sulfonic acid polyethylene polyvinyl alcohol and reaction monomer N, N-diomyetal cyanocyline free radical polymerization to prepare a gel polymer electrolytic substrate material. After absorbing a small amount of organic electrolyte, the material is It can show higher ion conductivity while maintaining good mechanical strength.

Benefits of technology

In the case of absorbing a small amount of organic electrolyte, it shows a higher ion conductivity, while maintaining a good mechanical strength, and solving the contradiction between the electrolyte conductivity of gel polymer electrolyte and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003570272160000031
    Figure BDA0003570272160000031
Patent Text Reader

Abstract

The present invention relates to a gel polymer electrolyte matrix material, an electrolyte and a battery, and belongs to the technical field of gel electrolytes. The technical problem solved by the present invention is to provide a gel polymer electrolyte matrix material. The gel polymer electrolyte matrix material is formed by free radical polymerization of organic sulfonate grafted polyvinyl alcohol and reactive monomers, wherein the reactive monomers include N,N-diethyl cyanoacrylamide. The gel polymer electrolyte matrix material of the present invention can be cast into a film by a common method, and the obtained film is impregnated with an organic electrolyte solution to obtain a gel polymer electrolyte membrane, which has a low liquid absorption rate, high ionic conductivity and good mechanical strength, and can be used as a polymer electrolyte to replace liquid electrolytes to improve the safety performance of lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a gel polymer electrolyte matrix material, an electrolyte and a battery, and belongs to the technical field of gel electrolytes. Background Art

[0002] Currently, lithium-ion batteries on the market mainly use organic electrolyte solutions as lithium ion conductive media. When the battery is overcharged, overheated, short-circuited, or impacted, safety accidents such as combustion and explosion are prone to occur.

[0003] In order to improve the safety of lithium-ion batteries, polymer electrolytes are used instead of liquid electrolytes as lithium-ion conducting media, which is an effective technical solution to improve the safety of lithium-ion batteries. The battery electroactive substances and working principles of the battery prepared by this polymer electrolyte are basically the same as those of liquid lithium-ion batteries, but it does not use free electrolytes, but solid or semi-solid polymer electrolytes, which overcome the problems of easy leakage, short circuit, poor safety, etc. of liquid electrolyte batteries.

[0004] All-solid-state polymer electrolytes are mainly made by dissolving lithium salts in high molecular weight polymers such as polyethylene oxide or polypropylene oxide. Such polymer electrolytes are usually prepared by solvent evaporation coating technology. The polymer matrix mainly includes polyethers and polyethers and polysilanes, polyphosphides homopolymers or copolymers. Since the ion conduction in this polymer electrolyte is achieved through the segmental movement of polymer molecules, its ion conductivity at room temperature is low, generally not exceeding 10 -5 Scm -1 , but it does not have commercial application value yet.

[0005] Gel polymer electrolytes are usually composed of a polymer matrix, a plasticizer, and an electrolyte lithium salt. The organic solvent of the electrolyte solution and the electrolyte lithium salt are solidified together in the network structure of the polymer matrix to achieve ion conduction. The ionic conductivity of the gel polymer electrolyte increases with the increase in the content of the electrolyte solution. Under high electrolyte solution content conditions, the conductivity can be close to the ionic conductivity of the liquid electrolyte and is much higher than the conductivity of the all-solid polymer electrolyte. Although gel polymer electrolytes with high electrolyte solution content help improve battery performance, they lead to poor mechanical strength of the gel polymer electrolyte, which does not help improve the safety performance of the battery, and loses the original intention of gel polymer electrolytes to improve the safety of lithium batteries. The contradiction between the ionic conductivity and mechanical properties of gel polymer electrolytes is an important issue that needs to be solved in the development of gel polymer electrolytes.

[0006] Gel polymer electrolytes usually use polymers with solubility parameters similar to those of the organic solvents in the electrolyte as the matrix, and the concentration used is 1.0 mol.L -1It is obtained by impregnating and swelling the polymer matrix with electrolyte. The ionic conductivity of polymer electrolyte is related to the number of free ions per unit volume. Only when the free ion concentration per unit volume is higher can the polymer electrolyte achieve a higher ionic conductivity. In order for the polymer electrolyte to achieve a conductivity that meets the requirements of battery use, the absorption amount of the organic electrolyte must be 300-500% of the weight of the polymer matrix itself. At such a high absorption amount of the electrolyte, since the solvent of the electrolyte is also a good solvent for the polymer matrix and they are mutually soluble, the cohesive energy of the polymer matrix is ​​reduced under the action of the good solvent, resulting in a rapid decrease in the mechanical strength of the polymer electrolyte and a deterioration in the mechanical properties. Summary of the invention

[0007] In view of the above defects, the technical problem solved by the present invention is to provide a gel polymer electrolyte matrix material, which can exhibit high ion conductivity while maintaining good mechanical strength by absorbing only a small amount of organic electrolyte.

[0008] The gel polymer electrolyte matrix material of the present invention is prepared by free radical polymerization of organic sulfonate grafted polyvinyl alcohol and reactive monomers, wherein the reactive monomers include N,N-diethylcyanoacrylamide.

[0009] In one embodiment of the present invention, the weight of N,N-diethyl cyanoacrylamide is 50-200% of the weight of the organic sulfonate grafted polyvinyl alcohol. In a preferred embodiment, the weight of N,N-diethyl cyanoacrylamide is 100-150% of the weight of the organic sulfonate grafted polyvinyl alcohol.

[0010] In one embodiment of the present invention, the organic sulfonate grafted polyvinyl alcohol is prepared by the following method: after irradiation activation of polyvinyl alcohol, grafting reaction with organic sulfonate monomer is carried out to obtain organic sulfonate grafted polyvinyl alcohol, and the weight of organic sulfonate monomer is 5-150% of the weight of polyvinyl alcohol.

[0011] In a preferred embodiment, the weight of the organic sulfonate monomer is 15-50% of the weight of the polyvinyl alcohol.

[0012] In a specific embodiment, the degree of polymerization of polyvinyl alcohol is 500-4000, and the degree of hydrolysis is 50%-99%; preferably, the degree of polymerization of polyvinyl alcohol is 1500-2800, and the degree of hydrolysis is 70%-90%.

[0013] In one embodiment, the radiation source for irradiation activation is 60 Coy rays or electron beams, the dose of irradiation activation is 5 to 50 KGy.

[0014] In a specific embodiment, the grafting reaction temperature is 30 to 90° C. and the time is 4 to 24 hours.

[0015] In some embodiments, the organic sulfonate monomer includes at least one of sodium vinyl sulfonate, sodium allyl sulfonate, sodium methacrylic sulfonate, 2-acrylamide-2-methylpropane sulfonic acid, and sodium styrene sulfonate.

[0016] Furthermore, the reactive monomers of the present invention also include acrylic ester monomers.

[0017] In some embodiments, the acrylate monomer has a chemical formula of at least one of CH2=CR1COOR2, wherein R1 is -H or -CH3, and R2 is -(CH2) n CH3, n=an integer from 0 to 12.

[0018] In some specific embodiments, the weight of the acrylic ester monomer is 10-60% of the weight of N,N-diethylcyanoacrylamide.

[0019] The invention also provides a gel polymer electrolyte.

[0020] The gel polymer electrolyte of the present invention comprises a polymer matrix and an electrolyte lithium salt, wherein the polymer matrix is ​​the gel polymer electrolyte matrix material of the present invention.

[0021] The invention also provides a gel polymer battery.

[0022] The gel polymer battery of the present invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is the gel polymer electrolyte of the present invention.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] Conventional preparation methods of gel polymer electrolytes, whether using commercial polymer substrates or polymerizing the required polymer substrates from monomers, use a large amount of organic solvents as a medium, which inevitably pollutes the production environment. The production process of the polymer electrolyte of the present invention uses water as a medium, which is pollution-free to the environment and harmless to the health of the operating production personnel, and is a green and environmentally friendly production technology.

[0025] The gel polymer electrolyte matrix material of the present invention can be cast into a film by a common method. After the obtained film is impregnated with an organic electrolyte solution, a gel polymer electrolyte membrane is obtained, and its liquid absorption rate is less than 200%, and the ionic conductivity is 10 -4 ~10 - 3 Scm -1 It also has good mechanical strength and can be used as a polymer electrolyte to replace liquid electrolyte to improve the safety performance of lithium-ion batteries.

[0026] The gel polymer electrolyte matrix material of the present invention has low raw material cost, simple preparation method, no need to rely on special equipment, low cost, and is conducive to industrial production. DETAILED DESCRIPTION

[0027] The technical approach to solve the contradiction between the ionic conductivity and mechanical properties of gel polymer electrolytes is: the first focus is to increase the polymer matrix itself, which should contain a large number of dissociable ion sources; secondly, the polymer matrix should contain components that can complex or chelate metal ions, and the metal complexes or chelates are conducive to the generation of free ions under the action of solvents; thirdly, the polymer matrix should be a highly polar polymer that is compatible with but not soluble in the solvent, so as to avoid a significant decrease in the mechanical properties of the material due to the effect of the solvent.

[0028] Based on the above technical approach to solving the mechanical properties of polymer electrolytes, the present invention provides a polymer electrolyte material and a preparation method thereof. The polymer electrolyte only needs to absorb a small amount of organic electrolyte to exhibit high ionic conductivity while maintaining good mechanical strength.

[0029] The gel polymer electrolyte matrix material of the present invention is prepared by free radical polymerization of organic sulfonate grafted polyvinyl alcohol and reactive monomers, wherein the reactive monomers include N,N-diethylcyanoacrylamide.

[0030] The gel polymer electrolyte matrix material of the present invention can be cast into a film by a common method. After the obtained film is impregnated with an organic electrolyte solution, a gel polymer electrolyte membrane is obtained, and its liquid absorption rate is less than 200%, and the ionic conductivity is 10 -4 ~10 - 3 Scm -1 It also has good mechanical strength and can be used as a polymer electrolyte to replace liquid electrolyte to improve the safety performance of lithium-ion batteries.

[0031] Among them, the structural formula of N,N-diethylcyanoacrylamide (abbreviated as BCEAM) is:

[0032]

[0033] BCEAM can be prepared by a common synthesis method in the art. In a specific embodiment, BCEAM is synthesized by Michael addition reaction using acrylamide and acrylonitrile as raw materials. The beneficial effect of introducing BCEAM in the present invention is that the nitrile group of the BCEAM monomer has unbonded lone pairs of electrons, which have strong coordination ability with metal ions to form a complex. This nitrile group and metal ion complex itself has ionic conductivity, which is very beneficial to improving the conductivity of the polymer electrolyte.

[0034] In one embodiment of the present invention, the weight of N,N-diethyl cyanoacrylamide is 50-200% of the weight of the organic sulfonate grafted polyvinyl alcohol. In a preferred embodiment, the weight of N,N-diethyl cyanoacrylamide is 100-150% of the weight of the organic sulfonate grafted polyvinyl alcohol.

[0035] In one embodiment of the present invention, the organic sulfonate grafted polyvinyl alcohol is prepared by the following method: after irradiation activation of polyvinyl alcohol, grafting reaction with organic sulfonate monomer is carried out to obtain organic sulfonate grafted polyvinyl alcohol, and the weight of organic sulfonate monomer is 5-150% of the weight of polyvinyl alcohol.

[0036] Organic sulfonate side chains are introduced into the polyvinyl alcohol molecular chain by radiation grafting. Under the solvation effect, the sulfonate is easy to ionize to generate free metal ions, which is beneficial to increase the unit body and free ion concentration of the polymer electrolyte.

[0037] In a preferred embodiment, the weight of the organic sulfonate monomer is 15-50% of the weight of the polyvinyl alcohol.

[0038] The polyvinyl alcohol described in the present invention is abbreviated as PVA, preferably has a degree of polymerization of 500-4000 and a degree of hydrolysis of 50%-99%. More preferably, the degree of polymerization of the polyvinyl alcohol is 1500-2800 and the degree of hydrolysis is 70%-90%. The PVA selected in the present invention has no solubility in organic carbonate solvents and can provide high mechanical strength support as a matrix of the polymer electrolyte.

[0039] In a specific embodiment, the radiation source for irradiation activation is 60 Coy rays or electron beams, the dose of irradiation activation is 5 to 50 KGy.

[0040] In one embodiment of the present invention, the grafting reaction temperature is 30 to 90° C. and the time is 4 to 24 hours.

[0041] The organic sulfonate monomers commonly used in the art are all suitable for the present invention. In a specific embodiment, the organic sulfonate monomer includes at least one of sodium vinyl sulfonate, sodium allyl sulfonate, sodium methacrylic sulfonate, 2-acrylamide-2-methylpropane sulfonic acid, and sodium styrene sulfonate.

[0042] Furthermore, the reactive monomers also include acrylate monomers. Adding acrylate monomers to the polymer can adjust the electrolyte solution absorption of the polymer electrolyte membrane and the flexibility of the polymer electrolyte membrane.

[0043] The commonly used acrylic acid ester monomers in the art are suitable for the present invention. In some specific embodiments, the acrylic acid ester monomer has a chemical formula of at least one of CH2=CR1COOR2, wherein R1 is -H or -CH3, and R2 is -(CH2) n CH3, n=an integer from 0 to 12. In some specific embodiments, the acrylic acid ester monomer includes at least one of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, vinyl acetate, 2-ethylhexyl acrylate, and the like.

[0044] In some specific embodiments, the weight of the acrylic ester monomer is 10-60% of the weight of N,N-diethylcyanoacrylamide.

[0045] The gel polymer electrolyte matrix material of the present invention can be obtained by a common polymerization method. In a specific embodiment, it is prepared by the following method:

[0046] First, commercially available PVA is irradiated and activated with a high-energy radiation source to form a free radical active center; then, deionized water and an organic monomer containing a sulfonate group are added to a glass reaction bottle equipped with a stirring, heating and condensing device, and then the irradiated activated PVA is added to carry out a grafting reaction at a temperature of 30 to 90° C. for 4 to 24 hours to obtain an organic sulfonate monomer grafted PVA aqueous solution; then, N,N-diethylcyanoacrylamide (BCEAM) monomer is added to the aqueous solution of the sulfonate organic monomer grafted PVA for free radical initiated polymerization to obtain a BCEAM polymer emulsion; or any one or more ester monomers are added for copolymerization to obtain a poly-BCEAM-ester monomer copolymer emulsion; that is, a gel polymer electrolyte matrix material emulsion.

[0047] In a preferred embodiment, the synthesized poly-BCEAM emulsion or BCEAM-ester monomer copolymer emulsion is cast into a film, the water is dried and vacuum-heated to obtain a gel polymer electrolyte matrix material film. The film is impregnated with an organic electrolyte solution to obtain a liquid absorption rate of less than 200% and an ionic conductivity of 10 -4 ~10 -3 Scm -1 And a polymer electrolyte membrane with good mechanical strength.

[0048] Specifically, the following method is used for preparation:

[0049] 1. Synthesis of BCEAM: Add acrylamide to a three-necked flask, then add dioxane solvent and stir until completely dissolved, add sodium hydroxide as a catalyst, and then slowly add acrylonitrile dropwise. The reaction temperature is controlled in the range of 30-50°C. The final product is a light yellow transparent viscous liquid.

[0050] 2. Preparation method of organic sulfonate grafted PVA aqueous solution: first, commercially available PVA is irradiated and activated with a high-energy radiation source to form free radical active centers; deionized water and organic sulfonate monomers are added to a glass reaction bottle equipped with a stirring, heating and condensing device, and then the irradiated activated PVA is added, and the grafting reaction is carried out at a temperature of 30 to 90°C for 4 to 24 hours.

[0051] 3. Preparation method of BCEAM polymer emulsion: After the poly-grafting reaction in step (2) is completed, add BCEAM monomer or add BCEAM and ester monomer simultaneously according to the metered amount and stir and mix, adjust the reaction temperature to 60-85°C, and then add ammonium persulfate to initiate polymerization for 6-36 hours.

[0052] 4. Take part of the prepared BCEAM polymer emulsion and pour it into a plastic container. First, dry the water in a forced air oven at 80-90°C, and then transfer it to a vacuum oven at 85-90°C for vacuum drying for 24 hours. The vacuum dried sample is stored in a desiccator for later use.

[0053] The invention also provides a gel polymer electrolyte.

[0054] The gel polymer electrolyte of the present invention comprises a polymer matrix and an electrolyte salt, wherein the polymer matrix is ​​the gel polymer electrolyte matrix material of the present invention.

[0055] The electrolyte salt may be a commonly used electrolyte salt in the present invention, such as a lithium salt. In a specific embodiment of the present invention, the electrolyte salt is LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LIFSI (lithium bis(fluorosulfonyl)imide), LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiBOB (lithium dioxalate borate), LiDFOB (lithium difluoroborate oxalate), LiPF2O2 (lithium difluorophosphate), etc.

[0056] The gel polymer electrolyte of the present invention is prepared by conventional methods. In one embodiment of the present invention, the gel polymer electrolyte matrix material is cast into a film, and then immersed in an electrolyte, and then immersed in the electrolyte at 70°C for 24 hours to obtain the electrolyte. The electrolyte is a conventional electrolyte in the art, including but not limited to LiTFSI / PC (propylene carbonate) electrolyte.

[0057] The invention also provides a gel polymer battery.

[0058] The gel polymer battery of the present invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is the gel polymer electrolyte of the present invention.

[0059] The gel polymer battery may be a lithium storage battery, and the positive electrode and negative electrode of commonly used lithium batteries are both suitable for the present invention.

[0060] The specific implementation modes of the present invention are further described below in conjunction with embodiments, but the present invention is not limited to the scope of the embodiments.

[0061] Example 1

[0062] 1. Synthesis of BCEAM: 800 g of dioxane, 432 g of acrylamide and 2 g of sodium hydroxide were added to a glass reaction bottle equipped with a stirring, heating and condensing device, and heated to 40°C. When the temperature was constant, 640 g of acrylonitrile was added dropwise for 6 to 8 hours. The reaction temperature was controlled in the range of 40 to 50°C. After the addition of acrylonitrile was completed, the reaction was continued at a constant temperature of 45°C for 16 hours. The final product conversion rate was about 95.0% and the concentration was 54.3%. The obtained BCEAM dioxane solution was a yellow viscous substance.

[0063] 2. Preparation of BCEAM polymer emulsion: 400g of water and 60g of 25% sodium vinyl sulfonate aqueous solution were added to a glass reaction bottle equipped with a stirring, heating and condensing device, and nitrogen was passed through for deoxygenation for 2.5 hours. Then, 45g of PVA with a degree of polymerization of 2400 activated by radiation was added, and the temperature was raised to 50°C for reaction for 12 hours. Then, 110g of the BCEAM solution synthesized in step 1 and 10g of 10% aqueous solution of ammonium persulfate as an initiator were added, the reaction temperature was adjusted to 75°C and the reaction was continued for 4 hours to obtain a light yellow polymer emulsion with a solid content of 19.0%.

[0064] 3. Weigh 10 g of polymer emulsion into a plastic container, first dry the water in a blast oven at 80-90°C, then transfer to a vacuum oven and dry at 85-90°C for 24 hours, then immerse the sample with a thickness of about 0.5 mm in LiTFSI / PC electrolyte. After soaking in the electrolyte at 70°C for 24 hours, the liquid absorption rate and conductivity of the polymer electrolyte membrane are measured as shown in Table 1.

[0065] Among them, the liquid absorption rate of polymer electrolyte membrane electrolyte is determined as follows:

[0066] The vacuum-dried sample was weighed and immersed in a 30% lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) electrolyte in propylene carbonate (PC), and then taken out and weighed after soaking at 70°C for 24 hours. Sample liquid absorption rate:

[0067] Liquid absorption rate % = (weight after immersion - weight before immersion) / weight before immersion x 100%.

[0068] Conductivity determination of polymer electrolyte membrane:

[0069] The ionic conductivity of the polymer electrolyte membrane that has absorbed the electrolyte is tested using an electrochemical impedance spectroscopy.

[0070] Example 2

[0071] 450g of water and 15g of sodium styrene sulfonate were added to a glass reaction bottle equipped with a stirring, heating and condensing device. After nitrogen was passed through to deoxygenate for 2.5 hours, 45g of PVA with a degree of polymerization of 2400 activated by irradiation was added, and the temperature was raised to 50°C for reaction for 12 hours. Then, 110g of the BCEAM solution synthesized in Example 1 and 10g of a 10% aqueous solution of ammonium persulfate as an initiator were added, the reaction temperature was adjusted to 75°C and the reaction was continued for 4 hours to obtain a milky white polymer emulsion with a solid content of 18.5%.

[0072] 10 g of polymer emulsion was weighed and poured into a plastic container. The water was first dried in a blast oven at 80-90°C, and then transferred to a vacuum oven and dried at 85-90°C for 24 hours. Then, a sample with a thickness of about 0.5 mm was immersed in LiTFSI / PC electrolyte. After soaking in the electrolyte at 70°C for 24 hours, the liquid absorption rate and conductivity of the polymer electrolyte membrane were measured as shown in Table 1.

[0073] Example 3

[0074] 450g of water and 15g of 2-acrylamide-2-methylpropanesulfonic acid were added to a glass reaction bottle equipped with a stirring, heating and condensing device, and nitrogen was passed through to deoxygenate for 2.5 hours. Then, 45g of PVA with a degree of polymerization of 2400 activated by radiation was added, and the temperature was raised to 50°C for reaction for 12 hours, and then 3.5g of lithium hydroxide was used to neutralize the mixture to a pH of about 7. Then, 110g of the BCEAM solution synthesized in Example 1 and 10g of a 10% aqueous solution of ammonium persulfate as an initiator were added, the reaction temperature was adjusted to 75°C, and the reaction was continued for 4 hours to obtain a light yellow polymer emulsion with a solid content of 18.2%.

[0075] 10 g of polymer emulsion was weighed and poured into a plastic container. The water was first dried in a blast oven at 80-90°C, and then transferred to a vacuum oven and dried at 85-90°C for 24 hours. Then, a sample with a thickness of about 0.5 mm was immersed in LiTFSI / PC electrolyte. After soaking in the electrolyte at 70°C for 24 hours, the liquid absorption rate and conductivity of the polymer electrolyte membrane were measured as shown in Table 1.

[0076] Example 4

[0077] 570g of water and 15g of 2-acrylamide-2-methylpropanesulfonic acid were added to a glass reaction bottle equipped with a stirring, heating and condensing device, and nitrogen was passed through to deoxygenate for 2.5 hours, and then 45g of PVA with a degree of polymerization of 2400 activated by radiation was added, and the temperature was raised to 50°C for reaction for 12 hours, and then 3.5g of lithium hydroxide was used to neutralize the mixture to a pH of about 7. Then 110g of the BCEAM solution synthesized in Example 1, 26g of methyl acrylate and 10g of a 10% aqueous solution of ammonium persulfate as an initiator were added, the reaction temperature was adjusted to 75°C and the reaction was continued for 4 hours to obtain a milky white polymer emulsion with a solid content of 17.8%.

[0078] 10 g of polymer emulsion was weighed and poured into a plastic container. The water was first dried in a blast oven at 80-90°C, and then transferred to a vacuum oven and dried at 85-90°C for 24 hours. Then, a sample with a thickness of about 0.5 mm was immersed in LiTFSI / PC electrolyte. After soaking in the electrolyte at 70°C for 24 hours, the liquid absorption rate and conductivity of the polymer electrolyte membrane were measured as shown in Table 1.

[0079] Example 5

[0080] The preparation method and composition ratio of the polymer electrolyte membrane of this embodiment are the same as those of embodiment 4, the only difference being that vinyl acetate is used instead of methyl acrylate.

[0081] Example 6

[0082] The preparation method and composition ratio of the polymer electrolyte membrane of this embodiment are the same as those of embodiment 4, the only difference being that isooctyl acrylate is used instead of methyl acrylate.

[0083] Example 7

[0084] The preparation method and composition ratio of the polymer electrolyte membrane of this embodiment are the same as those of Embodiment 1, the only difference being that 165 g of the BCEAM solution synthesized in Embodiment 1 is added.

[0085] Example 8

[0086] The preparation method and composition ratio of the polymer electrolyte membrane of this embodiment are the same as those of Embodiment 1, except that 140 g of the BCEAM solution synthesized in Embodiment 1 is added.

[0087] Example 9

[0088] The preparation method and composition ratio of the polymer electrolyte membrane of this embodiment are the same as those of Embodiment 2, the only difference being that the amount of PVA used is 52 g and the amount of sodium styrene sulfonate used is 8 g.

[0089] Example 10

[0090] The preparation method and composition ratio of the polymer electrolyte membrane of this embodiment are the same as those of Embodiment 2, the only difference being that the amount of PVA used is 40 g and the amount of sodium styrene sulfonate used is 20 g.

[0091] Table 1 Absorption rate and conductivity of polymer electrolyte membrane electrolyte

[0092] Example Electrolyte absorption rate % <![CDATA[Conductivity Scm -1 > Example 1 89.4 <![CDATA[1.47×10 -4 ]]> Example 2 70.8 <![CDATA[1.05×10 -4 ]]> Example 3 82.7 <![CDATA[1.35×10 -4 ]]> Example 4 143.5 <![CDATA[6.56×10 -4 ]]> Example 5 160.3 <![CDATA[4.75×10 -4 ]]> Example 6 128.2 <![CDATA[5.56×10 -4 ]]> Example 7 118.6 <![CDATA[3.24×10 -4 ]]> Example 8 105.2 <![CDATA[2.63×10 -4 ]]> Example 9 68.6 <![CDATA[0.96×10 -4 ]]> Example 10 75.2 <![CDATA[1.21×10 -4 ]]>

[0093] It is well known that the mechanical strength of plasticized polymer films decreases with the increase of plasticizer content. Gel polymer electrolytes prepared from polymer materials such as polyvinylidene, polyacrylonitrile, and polymethyl methacrylate need to absorb electrolyte solution of more than 500% of the polymer weight to achieve a conductivity of 10 -4 Scm -1 , at this time, the mechanical strength of the gel polymer electrolyte is very low and the tear resistance is very poor. The test results of Table 1 on the absorption rate and conductivity of the polymer electrolyte membrane show that the absorption rate of the polymer electrolyte of the present invention is less than 200%, and its conductivity can be as high as 6.56×10 -4 Scm -1 At this time, the polymer electrolyte membrane has excellent mechanical strength and elastic deformation.

Claims

1. Gel polymer electrolyte matrix material, characterized in that: It is formed by free radical polymerization of organic sulfonate grafted polyvinyl alcohol and reactive monomers, wherein the reactive monomers include N,N-diethyl cyanoacrylamide; the weight of N,N-diethyl cyanoacrylamide is 50-200% of the weight of the organic sulfonate grafted polyvinyl alcohol; in the organic sulfonate grafted polyvinyl alcohol, the weight of the organic sulfonate monomer is 5-150% of the weight of the polyvinyl alcohol, and the polymerization degree of the polyvinyl alcohol is 500-4000.

2. The gel polymer electrolyte matrix material according to claim 1, characterized in that: The weight of N,N-diethyl cyanoacrylamide is 100-150% of the weight of the organic sulfonate grafted polyvinyl alcohol.

3. The gel polymer electrolyte matrix material according to claim 1, characterized in that: The organic sulfonate grafted polyvinyl alcohol is prepared by the following method: after the polyvinyl alcohol is activated by radiation, a grafting reaction is carried out with an organic sulfonate monomer to obtain the organic sulfonate grafted polyvinyl alcohol.

4. The gel polymer electrolyte matrix material according to claim 3, characterized in that: The weight of the organic sulfonate monomer is 15-50% of the weight of the polyvinyl alcohol.

5. The gel polymer electrolyte matrix material according to claim 3, characterized in that: The degree of hydrolysis of polyvinyl alcohol is 50% to 99%.

6. The gel polymer electrolyte matrix material according to claim 5, characterized in that: The degree of polymerization of polyvinyl alcohol is 1500-2800, and the degree of hydrolysis is 70%-90%.

7. The gel polymer electrolyte matrix material according to claim 3, characterized in that: The radiation source for irradiation activation is 60 Coγ-ray or electron beam, the irradiation activation dose is 5 to 50 kGy.

8. The gel polymer electrolyte matrix material according to claim 3, characterized in that: The grafting reaction temperature is 30 to 90° C., and the time is 4 to 24 hours.

9. The gel polymer electrolyte matrix material according to claim 3, characterized in that: The organic sulfonate monomer includes at least one of sodium vinyl sulfonate, sodium allyl sulfonate, sodium methacrylic sulfonate, 2-acrylamide-2-methylpropane sulfonic acid, and sodium styrene sulfonate.

10. The gel polymer electrolyte matrix material according to claim 1, characterized in that: The reactive monomers also include acrylic ester monomers.

11. The gel polymer electrolyte matrix material according to claim 8, characterized in that: The chemical formula of the acrylic ester monomer is at least one of CH2=CR1COOR2, wherein R1 is -H or -CH3, and R2 is -(CH2) n CH3, n=0~12.

12. The gel polymer electrolyte matrix material according to claim 11, characterized in that: The weight of the acrylic acid ester monomer is 10-60% of the weight of N,N-diethylcyanoacrylamide.

13. A gel polymer electrolyte comprising a polymer matrix and an electrolyte lithium salt, characterized in that: The polymer matrix is ​​the gel polymer electrolyte matrix material according to any one of claims 1 to 12.

14. A gel polymer battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The electrolyte is the gel polymer electrolyte according to claim 13.

Citation Information

Patent Citations

  • Two-phase polymer electrolyte film for lithium ion battery and preparation method thereof

    CN101630760A

  • Graft copolymer water-based adhesive, preparation method thereof and application of graft copolymer water-based adhesive in silicon-carbon negative electrode

    CN113563531A

  • High polymer gel electrolyte and lithium secondary battery using it

    JP2000294284A